Philosophy and Engineering: An Emerging Agenda
XVIII, 361 p.
Keywords: Whereas science, technology, and medicine have all called forth dedicated philosophical investigations, a fourth major contributor to the technoscientific world in which we all live - that is, engineering - has been accorded almost none of the philosophical attention it deserves. This volume thus offers a first characterisation of this important new field, by some of the primary philosophers and ethicists interested in engineering and leading engineers interested in philosophical reflections. The volume deals with such questions as: What is engineering? In what respect does engineering differ from science? What ethical problems does engineering raise? By what ethical principles are engineers guided? How do engineers themselves conceive of their profession? What do they see as the main philosophical challenges confronting them in the 21st century? The authors respond to these and other questions from philosophical and engineering view points and so illustrate how together they can meet the challenges and realize the opportunities present in the necessary encounters between philosophy and engineering - encounters that are ever more important in an increasingly engineered world and its problematic futures.